SP-0027 Against the motion - V. Budach (Radiotherapy and Oncology, 2013)
Type 1 diabetes imposes a significant burden through morbidity, mortality, and high health care costs while also generating additional health, economic, and social costs, ranging from mental health conditions to risk of financial hardship to social stigma. Many of these outcomes may also spill over to families and caregivers. The economic literature increasingly recognizes the importance of including broader societal impacts in economic evaluations, including some guidelines for assessment of health interventions. However, in practice, societal impacts are incorporated in a limited way in assessments of type 1 diabetes therapies, most commonly through certain productivity-related measures, with limited consideration of broader impacts. In this article, we review the wider impacts of type 1 diabetes and examine how recent evaluations of novel technologies apply different perspectives. We find that economic assessments inconsistently incorporate broader societal impacts, such as psychosocial effects, informal caregiving, and long-term economic consequences. Consideration of a broader range of societal impacts may provide a more comprehensive evidence base for evaluating type 1 diabetes treatments and technologies, including in decisions related to their development, distribution, and reimbursement.